Attische Sarkophage aus Ephesos Mit einem Beitrag von Walter Prochaska - Kintrup, Carola (Holzhausen, 2017)
The study of the Attic sarcophagi from Ephesos throws a light on the tectonics, the ornaments, the iconography and the stylistic development as a basis for a relative chronology of the genre on site. The results of this study gain in importance as they can be correlated with chronologically "fixed" data - see the Aristides sarcophagus with its portrait and the associated inscription on the sarcophagus base. The results can be compared with other Attic sarcophagi and be applied to other genres of the imperial Attic sculpture, so that the importance of the Attic sarcophagi as one of the leading forms of the Greek sculpture of the imperial period is underlined.